Performance of Pamong Praja Police Units in Disciplining Students in Timang Gajah District Bener Meriah Regency - Muklir, Muklir; Mustika, Susi Diana (FISIP Universitas Malikussaleh, 2020)
Satpol PP is an element that supports the duties of the Regional Government in securing and implementing Regional Government policies that are specified in the field of public order and peace. The level of discipline of students in Bener Meriah Regency is decreasing at this time. Many students are truant and wandering around during study hours. This study aims to describe how the performance of Satpol PP in controlling students, what efforts are made to improve discipline, and how studentsâ€™ attitudes and behavior change after policing. This study uses a descriptive qualitative approach. The results showed that the performance of Satpol PP in controlling student discipline was good because Satpol PP always routinely patrols 8 times a month. However, there are several obstacles, such as the minimum budget and inadequate facilities and infrastructure so that the performance of Satpol PP is not optimal. The efforts made by Satpol PP to improve discipline, namely in collaboration with the Education Office and school officials, as well as socializing and providing appeals to cafe owners. Meanwhile, we found variations in changes in student attitudes and behavior.Â AbstrakSatpol PP merupakan unsur pendukung tugas Pemerintah Daerah dalam mengamankan dan melaksanakan kebijakan Pemerintah Daerah yang bersifat khusus di bidang ketentraman dan ketertiban umum. Pada saat ini tingkat kedisiplinan pelajar di Kabupaten Bener Meriah menurun dan banyak sekali dijumpai siswa yang membolos dan berkeliaran pada saat jam belajar berlangsung. Penelitian ini bertujuan untuk mendiskripsikan bagaimana kinerja Satpol PP dalam penertiban pelajar, upaya apa saja yang dilakukan dalam meningkatkan kedisiplinan, dan bagaimana perubahan sikap dan perilaku pelajar setelah dilakukan penertiban. Penelitian ini menggunakan pendektan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa kinerja Satpol PP dalam penertiban kedisiplinan pelajar sudah baik karena Satpol PP selalu rutin melakukan patroli selama 8 kali sebulan. Akan tetapi ada beberapa kendala seperti minimnya anggaran dan sarana prasarana yang belum memadai sehingga kinerja Satpol PP menjadi kurang maksimal. Adapun upaya yang dilakukan Satpol PP untuk meningkatkan kedisiplinan yaitu bekerjasama dengan Dinas Pendidikan dan pihak sekolah, serta melakukan sosialisasi dan memberikan himbauan kepada pemilik caffe dan warnet. Sedangkan untuk perubahan sikap dan perilaku pelajar sangat variatif.